Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Solve the equation: logx+log(x-2)=log(x+4).?
6 Answers
- alwbsokLv 710 years agoFavorite Answer
log(x) + log(x - 2) = log(x + 4)
log(x(x - 2)) = log(x + 4)
x(x - 2) = x + 4
x^2 - 2x = x + 4
x^2 - 3x - 4 = 0
(x - 4)(x + 1) = 0
x = 4 or x = -1
But, x = -1 is not a solution, since log(-1) and log(-3) are not defined. Thus, the one and only solution is x = 4.
- Steven AnguloLv 410 years ago
When we're dealing with the same base, log M + log N = log (M*N)
So:
log x+log(x-2)=log(x+4)
log [x(x-2)] = log (x+4)
Therefore,
x(x - 2) = x + 4
x^2 - 2x = x + 4
x^2 - 3x - 4 = 0
(x - 4)(x + 1) = 0
x1 = 4; x2 = -1
We toss out x2 = -1 because in the original equation we see that log x would be log of a negative number (same case for log (x-2) but as long as you see one case of a negative log in the equation then that's enough to toss out that answer).
Your answer then is x = 4
We can verify the answer by substituting x = 4 in the original equation, and both sides must be the same:
log 4 + log (4 - 2) = log (4 + 4)
log 4 + log 2 = log 8
log (4*2) = log 8
log 8 = log 8
(I used the same rule again). I hope this helps...
- MechEng2030Lv 710 years ago
log(x) + log(x - 2) = log(x + 4)
log(x(x - 2)) = log(x + 4)
x^2 - 2x = x + 4
x^2 - 3x - 4 = 0
(x - 4)(x + 1) = 0
x = 4, -1
However, use x = 4 since x = -1 causes a negative argument inside the log function.
- How do you think about the answers? You can sign in to vote the answer.
- 10 years ago
x(x-2) = x + 4
x^2 - 3x - 4 = 0
(x -4) (x + 1)
x = -1 (It's not a solution, is undefined)
x = 4 (This is the only solution)